The Dialectic between Islamic Law and the Social Reality of the Minangkabau Society: A Study of the Sociology of Law - Pratama, Agam; Herix, Herix; Heru, Heru (GIC Proceeding, 2024)
This paper examines the dialectic between Islamic law and the social reality of the Minangkabau society through the perspective of the sociology of law. The Minangkabau society, with its matrilineal culture, is an interesting subject to analyze in the context of the interaction between Islamic law and local culture. This study discusses the interaction between Islamic law and the matrilineal culture of the Minangkabau, and how social factors such as education level, socio-economic status, and local political dynamics influence the interpretation and implementation of Islamic law in that society. Furthermore, it identifies the challenges and efforts made to achieve harmony between Islamic law and the social reality of the Minangkabau society, involving the role of religious institutions, traditional authorities, local governments, educational institutions, and the community itself. These efforts include collaboration in conducting contextual ijtihad or Islamic legal reasoning, education and socialization about adaptive Islamic law, and the formation of regulations and policies that facilitate the application of Islamic law according to the cultural context of the Minangkabau. Through this study, a deeper understanding is gained of the role of Islamic law in the Minangkabau society, as well as the challenges and opportunities in implementing it in accordance with the unique socio-cultural context. The sociology of law provides a valuable perspective in the effort to achieve harmony between Islamic law and the social reality of society.